MEMAHAMI HADIS MUTAWATIR DAN HADIS AHAD - Suhartawan, Budi; Hasanah, Muizzatul (DIRAYAH : Jurnal Ilmu Hadis, 2022)
The problem of understanding the hadith of the Prophet is a very serious issue to be studied and discussed. This is because hadith is the second source of data for Islamic teachings after the holy Qur'an. This research was conducted with an epistemological approach which is part of the study of philosophy. The research data collection technique was carried out by library research with the content analysis method, which is a study that aims to analyze the content, know and understand the mutawatir hadith and the ahad hadith. Data analysis was carried out by descriptive method, which is a characteristic of research that reveals more comprehensively about various social and natural phenomena found in people's lives. The conclusion of this paper is that the mutawatir hadith is a hadith narrated by many credible (trustworthy) narrators and it is impossible to lie in congregation/public, while the Sunday hadith is a hadith where the number of narrators does not reach a strong number for argumentation. as contained in the mutawair hadith or hadith categorized as famous hadith.